Pharmacoeconomic analysis of the choice of antimicrobial drugs for the treatment of community-acquired pneumonia by physicians and final year medical students - V. G. Deriushkin; S. V. Gatsura (Izdatelstvo OKI, 2021)
The authors of the article conduct a pharmacoeconomic analysis of antimicrobial agents (AMA) prescriptions based on a survey of graduates of the medical faculty of a medical university and outpatient healthcare practitioners in Moscow. In addition to the pharmacoepidemiological part, the article also contains a pharmacoeconomic aspect to obtain a more complete picture, reflecting the choice of drugs not only in primary healthcare, but also among graduates of the medical faculty, who can potentially become its members without preliminary training in medical residency.The purpose of this study is to conduct a comparative pharmacoeconomic analysis of the AMA choice in the treatment of community-acquired pneumonia based on the data of a survey of general practitioners, district physicians and graduates of the medical faculty.Methodology. The 206 physicians took part in the anonymous voluntary survey.Results. 177 (85.9 %) of surveyed doctors were women and 62 (14.1 %) were men who made up Group 1. The average age of the surveyed doctors was 47.8±13.3 years, the average medical experience was 21.4±13.4 years. Group 2 consisted of 240 students, of which 178 were women (74.17 %) and 62 were men (25.83 %). The average age of the respondents in the group 2 was 24.8±3.3 years. When calculating the average cost of a treatment course of community-acquired pneumonia, depending on the structure of prescriptions, the value in Group 1 amounted to 420.82 rubles and 367.44 rubles in Group 2, while the share of costs for aminopenicillin drugs directly recommended for prescription to treat community-acquired pneumonia amounted to 8.35 and 4.97 %, respectively. Despite the current recommendations, respondents prefer to choose second-line AMAs, which are more expensive drugs. Respondents in both groups underestimate the first-line drugs that meet the current recommendations, namely aminopenicillins. Despite their low cost and ease of use in an outpatient setting, the frequency of their prescription remains low. The authors believe that more attention should be paid to the problem of rational use of antimicrobial agents. This problem can be solved through educational interventions at all levels of education, which can change the picture of drugs prescriptions in future, will allow practitioners and graduates of medical faculties to refer more often to clinical guidelines and patient treatment protocols. Comprehensive measures in this direction can not only positively affect the quality of medical care, but also reduce antibiotic resistance in the outpatient setting.